IDENTIFIKASI MISKONSEPSI SISWA PADA KONSEP FOTOSINTESIS DAN RESPIRASI TUMBUHAN - Kartika Fandiyani; Tri Jalmo; Rini Rita T. Marpaung (Universitas Lampung, 2017)
This research aim wasto describe students' misconception in the concept of plants photosynthesis and respiration and all factors that affected students' misconception. This research used descriptivedesign. The Samples were 351 SMP students of VIIIgrade at Tumijajar district academic year 2015/2016 which were chosen by using purposive sampling technique. Data were collectedby multipkle choicetest and student questionnaire. The test result were analyzed using the CRI, while the student questionnaire were analyzed using Pearson correlation test. The result of dataanalysis showed that students get misconception that was 57,30% with